INTENSITY OF FALL-ARMYWORM (SPODOPTERA LITURA FABRICIUS) PEST ATTACKS ON CAYENNE PEPPER (CAPSICUM FRUTESCENS) PLANTS IN KARST LAND - Handru, Alan; Putri, Diyona (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2024)
Agriculture is an important sector in global food needs. One of the plants that has high economic value in Indonesia is cayenne pepper (Capsicum frutescens). However, the productivity of cayenne pepper is often threatened by pest attacks, one of which is the fall-armyworm (Spodoptera litura), which can cause significant damage to plants. In karst areas such as Ponjong village, Gunung Kidul, Yogyakarta, pest management challenges become more complex due to unique environmental conditions. Karst has calcareous soil and limited water availability, which affects interactions between plants and pests. This research aims to understand the intensity of fall-armyworm attacks on cayenne pepper in karst areas and the environmental factors that influence these attacks. Using survey and field observation methods, this research found that the intensity of pest attacks varied in each plot, with an average percentage of plants attacked at 15.71%. High temperature, humidity and karst soil characteristics create an environment conducive to the development of fall armyworms. Therefore, an effective and sustainable control strategy is needed to support cayenne pepper productivity in karst areas.